Physical interpretation of impact bend test by means of mathematical methods - Ranatowski, Eugeniusz; Sadowski, Jan; Strzelecki, Ryszard (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the possibility to apply mathematical methods to process dynamic impact bend test diagrams in force-time (F - t) layout. The paper presents both a methodology of taking off "F - t" characteristics and a computer-aided testing stand, as well as processing algorithms of diagrams in the field of mathematical filtration based on averaging random variable and oscilation in the field of time and frequency.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka